2009
DOI: 10.1039/b805266b
|View full text |Cite
|
Sign up to set email alerts
|

The surface of neat water is basic

Abstract: Theoretical studies which conclude that the surface of neat water is acidic (with a pH < or = 4.8), due to the preferential adsorption of hydronium ions, are contrary to the available experimental evidence. Air bubbles in water have a negative charge, as do hydrophobic oil drops in water, and streaming potential measurements on inert surfaces such as Teflon in water show a similar negative surface charge. In each case the pH dependence of the zeta potential has an isoelectric point between pH 2-4. An isoelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
363
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(383 citation statements)
references
References 28 publications
(33 reference statements)
19
363
1
Order By: Relevance
“…Hydrophobic surfaces immersed in neutral pH water solutions of low salt concentrations typically acquire negative surface charge densities of about 10 -2 C m -2 (see Table II), as determined by streaming current experiments. 73,74 022119 Thus, dissociation of only a small fraction of the adsorbed water molecules would be sufficient to explain the observed maximal net charges densities, and it may also be sufficient for the roughly ten times higher charge densities observed here. Furthermore, it must be considered that water adsorption is increased at the swab contact site during rubbing due to capillary condensation, especially for hydrophilic polymer combinations, and will be even further enhanced, in a positive feed-back, due to electric field-adsorption of water once the swab apex has been charged, for both hydrophilic and hydrophobic polymers.…”
Section: B Water As a Source Of Triboelectric Chargementioning
confidence: 80%
See 1 more Smart Citation
“…Hydrophobic surfaces immersed in neutral pH water solutions of low salt concentrations typically acquire negative surface charge densities of about 10 -2 C m -2 (see Table II), as determined by streaming current experiments. 73,74 022119 Thus, dissociation of only a small fraction of the adsorbed water molecules would be sufficient to explain the observed maximal net charges densities, and it may also be sufficient for the roughly ten times higher charge densities observed here. Furthermore, it must be considered that water adsorption is increased at the swab contact site during rubbing due to capillary condensation, especially for hydrophilic polymer combinations, and will be even further enhanced, in a positive feed-back, due to electric field-adsorption of water once the swab apex has been charged, for both hydrophilic and hydrophobic polymers.…”
Section: B Water As a Source Of Triboelectric Chargementioning
confidence: 80%
“…However, adsorption of water is known to strongly increase its dissociation rate. 73 It is also conceivable that the shear force exerted on the water film or clusters by rubbing may promote further dissociation, as discussed in Sec. IV G. Under ambient air conditions, other ions such as HCO 3 − , CO 3 2 − , Na + , and Cl − , which are typically solved in adsorbed water films on insulator surfaces, 84 may also contribute to the charging.…”
Section: Water Dissociation and Ion Separationmentioning
confidence: 99%
“…Vácha et al (2008b) has suggested that techniques scrutinizing the water-gas interface from the vapor side can see it as acidic, while those examining it from the aqueous bulk side it will appear as basic. However, there seems little evidence in support as no experimental method has unambiguously shown that the surface is positive but several show it unambiguously as being negative (Hänni-Ciunel et al 2009;Beattie et al 2009). As hydroxide ions seem to be preferred over hydrogen ions, above a pH of about three, this generally reinforces the interface's negative charge compared with the bulk.…”
Section: Discussionmentioning
confidence: 99%
“…Both the oxonium ions and hydroxide ions have highly anisotropic hydrogen bonding that should increase their surface activity and relatively discourage bulk hydration compared with other ions. Beattie et al (2009) reported that the concentration of hydroxide present in homogenised oil in water is much greater than in neutral water, proving that there is increased autolysis driven by the adsorption of hydroxide ions at the oilwater interface in emulsions formed in oil-water (1.1 µm diameter, with surface 1.1 x 10 6 cm 2 L -1 ). Lützenkirchen et al (2008) put forward a model for the charging of hydrophobic electrolyte surfaces based upon enhanced autolysis within the structured interfacial water, with a pK w of about 7 and hence an isoelectric point of about pH 3.5.…”
Section: Figure 5 the H 2 O With 'Free' Dangling O-h (A1) Held By Twmentioning
confidence: 99%
See 1 more Smart Citation